Empowering Advanced Driver-Assistance Systems from Topological Data Analysis - Tarek Frahi; Francisco Chinesta; Antonio Falcó; Alberto Badias; Elias Cueto; Hyung Yun Choi; Manyong Han; Jean-Louis Duval (Mathematics, 2021)
We are interested in evaluating the state of drivers to determine whether they are attentive to the road or not by using motion sensor data collected from car driving experiments. That is, our goal is to design a predictive model that can estimate the state of drivers given the data collected from motion sensors. For that purpose, we leverage recent developments in topological data analysis (TDA) to analyze and transform the data coming from sensor time series and build a machine learning model based on the topological features extracted with the TDA. We provide some experiments showing that our model proves to be accurate in the identification of the state of the user, predicting whether they are relaxed or tense.